(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3YeQ Hf eMeO s)
(3ChdgG (B:s
(3JHOC HGdebGdI GdJGSYI hGdYTQjf ai JaSjQ CSeGA GdCOhjI bGd GdeDda Nda Hf YHGS GdRgGhi CcedJ LejY gPG GdcJGH GdYXje GdaGFOI s
(3BNQgG (B:s
(3aGQjahf hgh GdUfhHQI , heYfGg YTHI GdbdH jfShf (B: (3bjd gh GdSOGH s
(3fSNI SGHYIs
(3hJHOC HGdebGdI GdJGSYI hGdYTQjf ai JaSjQ CSeGA GdCOhjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
Keywords: (3GdWHs